Fe / TiO2 metal organic gel composite material as well as preparation method and application thereof

Fe/Ti metal organic gel was synthesized and calcined by a single-use hydrothermal method to prepare Fe/Ti2 metal organic gel composite material, which solved the problems of insufficient photocatalytic activity and low treatment efficiency in the prior art, and achieved efficient water contaminated by organic compounds.

CN119680650APending Publication Date: 2025-03-25NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510075418.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, when treating organic compounds contaminated water, especially tetracycline antibiotics contaminated water, there are problems of insufficient photocatalytic activity, low treatment efficiency and high cost.

Method used

The Fe/Ti metal organic gel was synthesized by a disposable hydrothermal method, and the Fe/TiO2 metal organic gel composite was obtained by calcination, which expanded its visible light absorption range and improved its specific surface area and catalytic activity.

Benefits of technology

This method not only improves the photocatalytic activity and visible light utilization rate of Fe/TiO2 composite materials, but also significantly enhances its adsorption and degradation ability to organic compounds and reduces treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680650A_ABST
    Figure CN119680650A_ABST
Patent Text Reader

Abstract

The invention provides a Fe / TiO2 metal organic gel composite material as well as a preparation method and application thereof, and belongs to the technical field of environmental protection. According to the preparation method, terephthalic acid, N, N-dimethylformamide, methanol, concentrated hydrochloric acid, 3-7 mmol of isopropyl titanate and 0.3-3.5 mmol of FeCl3. 6H2O are adopted as raw materials, and the Fe / Ti metal organic gel is synthesized by adopting a one-time hydrothermal method; and calcining the obtained Fe / Ti metal organic gel to obtain the Fe / TiO2 metal organic gel. The Fe / Ti metal organic gel obtained in the step (1) is calcined to obtain the Fe / TiO2 metal organic gel composite material. The composite material can effectively adsorb and degrade organic compounds, and has a good prospect in the aspect of treating tetracycline hydrochloride pollution in organic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental protection, and in particular to a method for preparing a Fe / TiO2 metal organic gel composite material, a Fe / TiO2 metal organic gel composite material prepared by the preparation method, and an application of the Fe / TiO2 metal organic gel composite material in deep oxidation degradation of organic compounds. Background Art

[0002] Water resources are a basic necessity for human survival. However, with the development of industrialization, water pollution caused by the widespread discharge of industrial wastewater has become a major environmental problem. Some organic compounds, such as tetracycline, a class of broad-spectrum antibiotics often used to treat bacterial infections, are also used as animal drugs. However, neither humans nor animals can fully absorb or transform them. Most antibiotics also penetrate into the environment through the food chain and have a significant impact on humans.

[0003] Wastewater containing organic compounds can be treated by advanced oxidation, membrane separation, adsorption and electrochemical techniques. Membrane separation technology has high requirements on water quality, because insoluble substances in water may clog the membrane, affecting its purity and reusability. Moreover, neither membrane separation nor adsorption can destroy the molecular structure of tetracycline, but can only reduce its concentration. Subsequent treatment of pollutants is still a problem. Electrochemical methods are more environmentally friendly, but are currently too expensive.

[0004] Deep oxidation has been widely used in the degradation of organic pollutants due to its rapid and efficient characteristics. In addition, deep oxidation is also seen as a very promising method for removing organic compounds from water. Deep oxidation based on SO4·- has better stability and performance. Persulfate can generate SO4·- and can be activated by adding transition metals.

[0005] Metal-organic frameworks (MOFs) have attracted attention in multiple research fields due to their high porosity, adjustable pore size and volume, and rich structural properties. Many researchers have combined iron-based MOFs with persulfate for the degradation of organic compounds. But the preparation process of most MOFs is usually time-consuming. Metal-organic gels have the same chemical properties as the corresponding MOFs. Their high porosity and large surface area make them advantageous for adsorption, catalysis, and other uses.

[0006] TiO2 is widely used in the photocatalytic degradation of organic pollutants. Anatase phase TiO2 has attracted attention due to its excellent photoelectric and photochemical properties. However, as a wide bandgap material, TiO2 has a narrow photoresponse range and photogenerated carriers are easy to recombine, which greatly limits its application. In order to improve the photocatalytic activity, researchers have explored a variety of modification strategies, including metal / non-metal doping, semiconductor coupling, and morphology control. Summary of the invention

[0007] In view of this, in order to improve the catalytic activity of TiO2 in the photocatalytic degradation of organic pollutants, on the one hand, the present invention provides a method for preparing a Fe / TiO2 metal organic gel composite material, which synthesizes the Fe / Ti metal organic gel by a one-time hydrothermal method. After calcination, the Fe / Ti metal organic gel not only has a porous structure and a high specific surface area, but also expands the visible light absorption range.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A method for preparing a Fe / TiO2 metal organic gel composite material comprises the following steps:

[0010] Step (1), preparation of Fe / Ti metal organic gel

[0011] The Fe / Ti metal organic gel was synthesized by a one-step hydrothermal method using terephthalic acid, N,N-dimethylformamide, methanol, concentrated hydrochloric acid, 3-7mmol isopropyl titanate and 0.3-3.5mmol FeCl3·6H2O as raw materials.

[0012] Step (2), preparation of Fe / TiO2 metal organic gel

[0013] The Fe / Ti metal organic gel obtained in step (1) is calcined to obtain Fe / TiO2 metal organic gel.

[0014] Preferably, the molar ratio of FeCl3·6H2O to isopropyl titanate is (1-5):10.

[0015] Preferably, the molar ratio of FeCl3·6H2O to isopropyl titanate is 3:10.

[0016] Preferably, in step (2), the calcination conditions are calcination at 300-600° C. for 1-3 h at a heating rate of 1-3° C. / min.

[0017] Preferably, in step (1), the one-time hydrothermal method is specifically:

[0018] 3-4 mmol of terephthalic acid is added to a mixed solution of 15-20 ml of N,N-dimethylformamide and 1-3 ml of methanol, and ultrasonically dispersed, and then 0.5-1 ml of concentrated hydrochloric acid and 3-7 mmol of isopropyl titanate are added, and stirred evenly, and finally 0-3.5 mmol of FeCl3·6H2O is added, and stirred evenly to obtain a mixed solution;

[0019] The mixed solution is transferred to a reaction kettle, kept at 120-180°C for 2-4 hours, cooled to room temperature, washed, and centrifuged to separate the precipitate to obtain a gel sample. The gel sample obtained by centrifugation is then vacuum dried at 50-70°C for 18-24 hours to obtain a Fe / Ti metal organic gel.

[0020] In a second aspect, the present invention can provide a Fe / TiO2 metal organic gel composite material, which is prepared according to the above-mentioned preparation method of the Fe / TiO2 metal organic gel composite material.

[0021] In a third aspect, the present invention also provides the use of the above Fe / TiO2 metal organic gel composite material in the deep oxidation degradation of organic compounds.

[0022] Preferably, a persulfate is added.

[0023] Preferably, the amount of persulfate added is 0.2-0.4 mmol.

[0024] Preferably, the persulfate is one of ammonium persulfate, sodium persulfate and potassium persulfate.

[0025] The preparation method of the Fe / TiO2 metal organic gel composite material provided by the present invention synthesizes the Fe / Ti metal organic gel by a one-time hydrothermal method, and obtains the Fe / TiO2 metal organic gel after calcination. Compared with the prior art, it has the following beneficial effects:

[0026] (1) The present invention synthesizes Fe / Ti metal organic gel by a one-time hydrothermal method, and obtains Fe / TiO2 metal organic gel after calcination, which not only has a porous structure and a high specific surface area, but also expands the visible light absorption range.

[0027] (2) Iron doping can effectively reduce the band gap, improve the utilization rate of visible light, and activate persulfate. The composite material can effectively adsorb and degrade organic compounds.

[0028] (3) The study found that the calcined Fe / TiO2 metal organic gel material not only has a porous structure and a high specific surface area, but also expands the visible light absorption range. The one-time hydrothermal method makes the distribution of Fe, Ti, O and C elements highly uniform. Among them, Fe and C are partially doped into the TiO2 lattice, which greatly improves the light response range of TiO2 and overcomes the shortcomings of easy recombination of photogenerated carriers. It can be foreseen that this material has good prospects in treating tetracycline hydrochloride pollution in organic wastewater.

[0029] (4) The Fe / TiO2 metal organic gel prepared by the present invention has a higher degradation effect on organic compounds than pure TiO2 and TiO2-MOG. In addition, Fe is cheap and doped Fe3+ ions. It can not only reduce the band gap and improve the utilization of visible light, but also activate persulfate. The presence of TiO2 can 3+ Converted to Fe 2+ , Fe 2+ Can activate persulfate to provide sufficient SO4 - 、·OH.

[0030] (5) Fe / TiO2 metal organic gel was prepared by one-step hydrothermal method and calcination. This method is simple, the conditions are relatively mild, the temperature is relatively low, and the synthesis time is shortened by nearly 5 times compared with the same type of MOF materials.

[0031] (6) The Fe / TiO2 metal organic gel composite material prepared by the present invention has a much larger specific surface area than pure TiO2 and TiO2-MOG, and can adsorb more organic compounds while providing more active sites to accelerate the reaction rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The UV-visible diffuse reflectance spectra of the composite materials prepared in Examples 1-5 and Comparative Example 1 of the present invention;

[0033] Figure 2 is the first-order adsorption kinetic equation of the composite material prepared in Examples 1-5 and Comparative Example 1 of the present invention;

[0034] Figure 3 A comparison of the adsorption reaction rate constant k of the composite materials prepared in Examples 1-5 of the present invention and Comparative Example 1 and under the influence of persulfate;

[0035] Figure 4 The first-order catalytic kinetic equations of the composite materials prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention and under the influence of persulfate;

[0036] Figure 5 Comparison of the catalytic reaction rate constant k of the composite materials prepared in Examples 1-5 of the present invention and Comparative Examples 1-3 and under the influence of persulfate;

[0037] Figure 6 This is a diagram showing the reuse of the tetracycline hydrochloride aqueous solution degradation experiment of Examples 1-5 of the present invention;

[0038] Figure 7 This is a diagram of the degradation mechanism of Examples 1-5 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0040] Example 1

[0041] Preparation of F / TM 50% (Fe:Ti=5:10)

[0042] 4mmol of terephthalic acid was added to a mixed solution of 20ml of N,N-dimethylformamide and 3ml of methanol, ultrasonicated for 20min, then 1ml of concentrated hydrochloric acid and 7mmol of isopropyl titanate were added, stirred for 10min, and finally 3.5mmol of FeCl3·6H2O was added and stirred for 30min. The hydrothermal reaction was carried out at 180℃ for 2h. The gel sample obtained by centrifugation was then dried at 50℃ for 24h. Finally, it was calcined at 600℃ for 2h in a muffle furnace at a heating rate of 3℃ / min to obtain Fe / TiO2 metal organic gel, named F / TM 50%.

[0043] In the catalytic reaction of tetracycline hydrochloride (TCH) organic compound, 0.4 mmol of persulfate (PS) is added, and the persulfate is ammonium persulfate.

[0044] Example 2

[0045] Preparation of F / TM 40% (Fe:Ti=4:10)

[0046] 3.8mmol terephthalic acid was added to a mixed solution of 16ml N,N-dimethylformamide and 2.5ml methanol, ultrasonicated for 20min, then 0.8ml concentrated hydrochloric acid and 4mmol isopropyl titanate were added, stirred for 10min, and finally 1.6mmol FeCl3·6H2O was added and stirred for 30min. The hydrothermal reaction was carried out at 120℃ for 4h. The gel sample obtained by centrifugation was then dried at 60℃ for 20h. Finally, it was calcined at 300℃ for 3h in a muffle furnace at a heating rate of 1℃ / min to obtain the desired product.

[0047] In the catalytic reaction of tetracycline hydrochloride (TCH) organic compound, 0.2 mmol of persulfate (PS) is added, and the persulfate is sodium persulfate.

[0048] Example 3

[0049] Preparation of F / TM 30% (Fe:Ti=3:10)

[0050] 3.6mmol terephthalic acid was added to a mixed solution of 18ml N,N-dimethylformamide and 2ml methanol, ultrasonicated for 20min, then 0.75ml concentrated hydrochloric acid and 5mmol isopropyl titanate were added, stirred for 10min, and finally 1.5mmol FeCl3·6H2O was added and stirred for 30min. The hydrothermal reaction was carried out at 150℃ for 3h. The gel sample obtained by centrifugation was then dried at 60℃ for 20h. Finally, it was calcined at 500℃ for 2h in a muffle furnace at a heating rate of 2℃ / min to obtain the desired product.

[0051] In the catalytic reaction of tetracycline hydrochloride (TCH) organic compound, 0.3 mmol of persulfate (PS) is added, and the persulfate is selected from potassium persulfate.

[0052] Example 4

[0053] Preparation of F / TM 20% (Fe:Ti=2:10)

[0054] 3.4mmol terephthalic acid was added to a mixed solution of 15ml N,N-dimethylformamide and 1.5ml methanol, ultrasonicated for 20min, then 0.6ml concentrated hydrochloric acid and 4mmol isopropyl titanate were added, stirred for 10min, and finally 0.8mmol FeCl3·6H2O was added and stirred for 30min. The hydrothermal reaction was carried out at 180℃ for 2h. The gel sample obtained by centrifugation was then dried at 70℃ for 18h. Finally, it was calcined at 400℃ for 3h in a muffle furnace at a heating rate of 3℃ / min to obtain the desired product.

[0055] In the catalytic reaction of tetracycline hydrochloride (TCH) organic compound, 0.4 mmol of persulfate (PS) is added, and the persulfate is ammonium persulfate.

[0056] Example 5

[0057] Preparation of F / TM 10% (Fe:Ti=1:10)

[0058] 3mmol terephthalic acid was added to a mixed solution of 15ml N,N-dimethylformamide and 1ml methanol, ultrasonicated for 20min, then 0.5ml concentrated hydrochloric acid and 3mmol isopropyl titanate were added, stirred for 10min, and finally 0.3mmol FeCl3·6H2O was added and stirred for 30min. The hydrothermal reaction was carried out at 120℃ for 4h. The gel sample obtained by centrifugation was then dried at 50℃ for 24h. Finally, it was calcined at 300℃ for 3h in a muffle furnace at a heating rate of 1℃ / min to obtain the desired product.

[0059] In the catalytic reaction of tetracycline hydrochloride (TCH) organic compound, 0.2 mmol of persulfate (PS) is added, and the persulfate is sodium persulfate.

[0060] Comparative Example 1

[0061] Preparation of TiO2-MOG

[0062] 3.6mmol terephthalic acid was added to a mixed solution of 18ml N,N-dimethylformamide and 2ml methanol, ultrasonicated for 20min, then 0.75ml concentrated hydrochloric acid and 5mmol isopropyl titanate were added, and stirred for 40min. The hydrothermal reaction was carried out at 150℃ for 3h. The gel sample obtained by centrifugation was then dried at 60℃ for 20h. Finally, it was calcined at 500℃ for 2h in a muffle furnace at a heating rate of 2℃ / min to obtain the desired product.

[0063] In the catalytic reaction of tetracycline hydrochloride (TCH) organic compound, 0.3 mmol of persulfate (PS) is added, and the persulfate is potassium persulfate.

[0064] Comparative Example 2

[0065] Preparation of F / TM 30% (Fe:Ti=3:10)

[0066] Same as Example 3, except that no persulfate (ammonium persulfate, sodium persulfate and potassium persulfate) is added in the catalytic reaction.

[0067] Comparative Example 3

[0068] Preparation of TiO2-MOG

[0069] The same as Comparative Example 1, except that no persulfate is added in the catalytic reaction.

[0070] Deep oxidation degradation of tetracycline hydrochloride:

[0071] 20 mg of each composite material prepared in Examples 1-5 and Comparative Examples 1-3 was mixed with 50 mL of tetracycline hydrochloride aqueous solution (40 mg / L) and stirred for 50 min without light to achieve adsorption and desorption equilibrium. Persulfate corresponding to Examples 1-5 and Comparative Examples 1-3 was subsequently added (as shown in Table 1 below). The catalytic process was started. In this experiment, a 300w xenon lamp was used to simulate sunlight to irradiate the reaction mixture, and magnetic stirring (400rpm) was performed. 3 ml of solution was taken after every 15 minutes. The resulting solution was then filtered through a 0.22 μm aqueous needle filter. The absorbance of the solution was measured at 357 nm using a UV-visible spectrophotometer to determine the content of tetracycline hydrochloride in the solution. The experiment was repeated three times, and the data obtained were the average of three times. The degradation efficiency was then calculated by the following formula.

[0072] Degradation efficiency (%) = 100 × (C0-Ct) / C0

[0073] Where C0 (mg / L) and Ct (mg / L) are the initial concentration of the solution and the concentration of the filtrate at degradation time t (min), respectively.

[0074] Table 1 Experimental data of Examples 1-5 and Comparative Examples 1-3

[0075]

[0076]

[0077] The UV-visible diffuse reflectance spectra (UV-vis DRS) of the composite materials prepared in Examples 1-5 and Comparative Example 1 are shown in Figure 1 . Compared with TiO2-MOG, the Fe-doped composites exhibit enhanced light absorption capabilities, which is mainly due to the transition after the coordination of the transition metal ions. In all prepared samples, the absorption edge of the composites was pushed to the long-wave direction, and the light absorption intensity was relatively strong. Importantly, the introduction of transition metals by doping will reduce the band gap of the material. Figure 1 As shown, the composite materials prepared in Examples 1-5 all have better visible light absorption capabilities.

[0078] The specific surface area, pore volume and average pore diameter of Examples 1-5 have obvious advantages over TiO2-MOG, as shown in Table 2 below.

[0079] Table 2 Specific surface area, pore volume and average pore diameter of Examples 1-5 and TiO2-MOG

[0080]

[0081]

[0082] The specific surface area, pore volume and average pore size of the composite materials prepared in Examples 1-5 of the present invention and Comparative Example 1 are shown in Table 2 above. It can be seen that the specific surface area of ​​Examples 1-5 is significantly higher than that of TiO2-MOG. The introduction of Fe significantly increases the number of micropores of TiO2-MOG, and the micropores can provide a larger specific surface area and pore volume, so that the adsorption amount of tetracycline hydrochloride by the composite material is greatly increased.

[0083] The first-order kinetic equation and adsorption reaction rate constant k of tetracycline hydrochloride adsorption in Examples 1-5 of the present invention and Comparative Example 1 are shown in Figure 2 and Figure 3As shown. The results show that the composite system has a large specific surface area and good pore structure, which improves its adsorption and catalytic ability. The adsorption reaction rate constant k can reach 4 times that of TiO2-MOG. It can be seen that the introduction of Fe significantly increases the adsorption amount of tetracycline hydrochloride by TiO2-MOG catalyst.

[0084] The first-order kinetic equation and catalytic reaction rate constant k of the catalytic degradation of tetracycline hydrochloride in Examples 1-5 and Comparative Examples 1-3 of the present invention are shown in FIG. Figure 4 and Figure 5 It can be seen that Examples 1-5 all have significant effects and are significantly greater than Comparative Examples 1-3. The photocatalytic degradation kinetic rates of F / TM 50%, F / TM 40%, F / TM 30%, F / TM 20% and F / TM 10% are 0.0402, 0.0495, 0.0536, 0.0477 and 0.0402 min, respectively. -1 Among them, the synergistic effect of F / TM 30% and persulfate showed the highest photocatalytic degradation kinetic rate (0.0536min -1 ). It is 30% higher than F / TM (0.004459min -1 ) (without persulfate addition) is 12.02 times larger than TiO2-MOG (0.00899 min-1), 5.96 times larger than TiO2-MOG with persulfate addition (0.00943 min-1). -1 ) is 5.68 times larger.

[0085] The stability and reuse of the composite materials of Examples 1-5 of the present invention are shown in Figure 6 . The stability of the composite material was tested using a three-cycle reaction. The composite material used in each experiment was recovered by centrifugation, washing and drying. After three cycles, the degradation rates of Examples 1-5 on TCH solution decreased, but were basically above 75%. This shows that Examples 1-5 have a relatively stable structure. The loss of effective components of the composite material during the centrifugation, washing and drying process may be the reason for the decrease in catalytic activity.

[0086] The degradation mechanism of the composite materials of Examples 1-5 of the present invention is shown in Figure 7 .

[0087] First, the specific surface area of ​​the composite materials in Examples 1-5 is large, providing many active sites for the reaction and accelerating the reaction process. At the same time, the composite materials generate e- and h+ by absorbing visible light, and the generated e- reacts with O2 adsorbed on the surface of the material to generate ·O2 - Since the CB potential of the material (-0.44) is higher than that of O2 / ·O2 - The (-0.33) is lower, so it can effectively produce O2 -In addition, e- can also react with Fe 3+ The reaction generates Fe 2+ , thereby promoting the reaction rate and ensuring the stability of the reaction cycle. 2+ Can significantly activate PS to generate SO4 - , and can also be used with Ti 4+ The reaction generates Ti 3+ .Ti 3 + It can also react with O2 to generate O2 - -OH can also react with h + The reaction generates ·OH. Finally, TCH is converted to SO4· - , OH, O2 - and h + Rapid degradation to form small molecular intermediates or H2O and CO2. The above reaction is relatively rapid, which is also an important reason why the prepared composite material can degrade organic compounds relatively quickly. At the same time, this composite material can also ensure a virtuous cycle of the reaction.

[0088] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of the present invention.

Claims

1. A method for preparing a Fe / TiO2 metal organic gel composite material, characterized in that: The steps include: Step (1), preparation of Fe / Ti metal organic gel The Fe / Ti metal organic gel was synthesized by a one-step hydrothermal method using terephthalic acid, N,N-dimethylformamide, methanol, concentrated hydrochloric acid, 3-7mmol isopropyl titanate and 0.3-3.5mmol FeCl3·6H2O as raw materials. Step (2), preparation of Fe / TiO2 metal organic gel The Fe / Ti metal organic gel obtained in step (1) is calcined to obtain Fe / TiO2 metal organic gel.

2. The method for preparing a Fe / TiO2 metal organic gel composite material according to claim 1, characterized in that: The molar ratio of FeCl3·6H2O to isopropyl titanate is (1-5):

10.

3. The method for preparing a Fe / TiO2 metal organic gel composite material according to claim 2, characterized in that: The molar ratio of FeCl3·6H2O to isopropyl titanate is 3:

10.

4. The method for preparing a Fe / TiO2 metal organic gel composite material according to claim 1, characterized in that: In step (2), the calcination conditions are calcination at 300-600° C. for 1-3 h at a heating rate of 1-3° C. / min.

5. A method for preparing a Fe / TiO2 metal organic gel composite material according to any one of claims 1 to 4, characterized in that: In step (1), the one-time hydrothermal method is specifically as follows: 3-4 mmol of terephthalic acid is added to a mixed solution of 15-20 ml of N,N-dimethylformamide and 1-3 ml of methanol, and ultrasonically dispersed, and then 0.5-1 ml of concentrated hydrochloric acid and 3-7 mmol of isopropyl titanate are added, and stirred evenly, and finally 0-3.5 mmol of FeCl3·6H2O is added, and stirred evenly to obtain a mixed solution; The mixed solution is transferred to a reaction kettle, kept at 120-180°C for 2-4 hours, cooled to room temperature, washed, and centrifuged to separate the precipitate to obtain a gel sample. The gel sample obtained by centrifugation is then vacuum dried at 50-70°C for 18-24 hours to obtain a Fe / Ti metal organic gel.

6. A Fe / TiO2 metal organic gel composite material, characterized in that: The Fe / TiO2 metal organic gel composite material is prepared according to the preparation method of any one of claims 1-5.

7. Use of the Fe / TiO2 metal organic gel composite material according to claim 6 in deep oxidation degradation of organic compounds.

8. The use according to claim 7, characterized in that: Add persulfate.

9. The use according to claim 8, characterized in that: The amount of persulfate added is 0.2-0.4 mmol.

10. The use according to claim 7 or 8, characterized in that: The persulfate is one of ammonium persulfate, sodium persulfate and potassium persulfate.